2005
DOI: 10.1007/s00277-004-0997-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 52 Indian patients with de novo myelodysplastic syndromes?a comparative analysis of results with reports from Asia

Abstract: Most published data on myelodysplastic syndromes (MDS) are derived from Western countries, which report MDS as a disease of the elderly. However, it was observed that Asian MDS patients were younger than subjects in Western reports. With this in mind, the study was conducted prospectively on 52 Indian patients to define chromosomal abnormalities and to understand ethno-geographical differences, if any, underlying the pathogenesis of MDS among this Asian population. Cytogenetic analysis was performed using GTG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…MDS prevalence increases with age, and the median age of patients at the time of diagnosis varies between 65 and 74 years (17). In our study, the median age of patients was 67 years.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…MDS prevalence increases with age, and the median age of patients at the time of diagnosis varies between 65 and 74 years (17). In our study, the median age of patients was 67 years.…”
Section: Discussionmentioning
confidence: 53%
“…Few reports have indicated geographical and ethnic differences in the frequency of specific chromosomal changes. The incidence of chromosomal abnormalities was between 37% and 88% in India and varied between 37% and 50% in China, Hong Kong, and Japan (17,18). Also, Haase et al (19) reported that the incidence of chromosomal abnormalities was 49% in Austria and Germany.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Complex aberrations have been more frequently observed in Indian patients as compared to those from other Asian countries. 13 As such, ethnic and/or geographical differences could be heterogeneous and contribute to clinical, cytogenetic or molecular events leading to MDS. Available reports on the incidence of MDS mostly originate from European countries, although major studies have been conducted in Japan.…”
mentioning
confidence: 97%
“…13 In addition, the frequency of chromosomal abnormalities varies between 37-50% in China, Thailand, Hong Kong and Japan. 13,14 Complex aberrations have been more frequently observed in Indian patients as compared to those from other Asian countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation